Implementasi Strategi Pemerintah Desa dalam Pengembangan Pariwisata di desa Winong kabupaten Tulungagung - Purnawati, Laily; Aprillianti, Veni (Universitas 17 Agustus 1945 Surabaya, 2023)
Against the background of the less than optimal development of Ngambal Lake tourism potential by the Winong village government, seen from the low number of visitors, the Winong village government wants to create a tourist destination again with a different concept, namely Jowin peak. In order to maintain its existence, the village government needs to create a strategy in developing and managing tourism potential. This research wants to analyze the strategy for developing and managing tourism potential created by the Winong village government. The qualitative approach is the research method chosen with the type of research being descriptive. The data collection used was interview and documentation methods. From the research results, it was concluded that the strategy for developing tourism potential in Winong village is through attraction aspects, transportation aspects and facility aspects to support Jowin peak tourism.